Nose-to-brain drug delivery by HS15 micelles for brain targeting of insoluble drug - Wei Zhang; Long Wan; Meiqi Han; Wen Guo; Zhiqi Wang; Xinyue Zhang; Xuyang Liu; Jiahao Wang; Yuling Mao (Acta Materia Medica)
Agomelatine (AGO) is an antidepressant with limited clinical application due to its low bioavailability caused by poor water solubility, severe hepatic degradation, and poor intracerebral distribution. Nanotechnology-based strategies constitute a powerful tool by utilizing drug solubility and targeted distribution to improve drug bioavailability in the brain tissues by nose-to-brain drug delivery. In the current study AGO was encapsulated within micelles using the commercially available Solutol HS15. As a result, AGO was efficiently loaded on the basis of least micelle size (14.17 ± 0.72 nm) and encapsulation efficiency (96.96%). In vivo and ex vivo experiments showed that micelles provided higher and more sustained brain distribution. And the results of pharmacokinetic experiments showed that micelles entered the brain region rapidly after intranasal administration and reach its peak within 0.25 h. The behavior of the nanoparticles indicated that the micelles were observed across the olfactory epithelium by examination of nasal mucosal penetration. The current study showed that HS15 micelles facilitate penetration of drugs in the olfactory epithelium and provide a system with which to target brain tissues and overcome the problem of inefficient drug delivery of insoluble drugs for central nervous system diseases.